Perinatal HIV Transmission Prevention: Challenges among Women Living with HIV in sub-Saharan Africa - Elizabeth Armstrong-Mensah, PhD; Krystal Ruiz, BSPH; Aminata Fofana, BSPH; Victoria Hawley (Global Health and Education Projects, Inc., 2020)
About 86 percent of the estimated 160,000 children newly-infected with the human immunodeficiency virus (HIV) live in sub-Saharan Africa. Despite global efforts to reduce perinatal HIV transmission, this phenomenon continues to be a public health problem in sub-Saharan Africa. This paper discusses challenges associated with perinatal HIV transmission prevention in sub-Saharan Africa and offers strategies for the way forward. These strategies include safe sex education and behavioral change, increased access to integrated antenatal care, training of unskilled traditional birth attendants into formal delivery systems, access to antiretroviral therapy, and investing in virologic testing. Key words: • HIV • Perinatal • Antiretroviral Therapy • Mother to Child HIV Transmission • HIV Prevention • Sub-Saharan Africa   Copyright © 2020 Armstrong-Mensah, et al. Published by Global Health and Education Projects, Inc. This is an open-access article distributed under the terms of the Creative Commons Attribution License (CC BY 4.0) which permits unrestricted use, distribution, and reproduction in any medium, provided the original work, first published in this journal, is properly cited.